Aluminum-lithium alloy powder and preparation method and application method thereof

By adding Li elements to aluminum-lithium alloy and adopting specific preparation methods, the problem of microcracks and low strength of aluminum-lithium alloy powder during the selected laser melting process is solved, and the effect of improving the additive manufacturing performance of aluminum alloy is achieved.

CN116037940BActive Publication Date: 2025-04-22CHANGSHA ADVANCED MATERIALS IND RES INST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211704564.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-29
Publication Date
2025-04-22
Estimated Expiration
2042-12-29

AI Technical Summary

Technical Problem

The existing aluminum-lithium alloy powders are prone to microcracks and low strength during the laser melting process of selected areas, which limits the promotion and application of aluminum-lithium alloy additive manufacturing technology.

Method used

Optimized aluminum-lithium alloy powder is prepared by adding Li elements to high-strength aluminum alloys and using specific alloy elements combinations and preparation methods, including intermediate-frequency furnace smelting, aerosol powder making and other steps.

Benefits of technology

The microstructure and phase structure of the selected laser-melted aluminum lithium alloy is improved, the stiffness and elastic modulus of additively manufactured aluminum alloys are improved, the density is reduced, and the surface smoothness and density of the molded samples are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116037940B_ABST
    Figure CN116037940B_ABST
Patent Text Reader

Abstract

The invention discloses an aluminum-lithium alloy powder, a preparation method thereof and an application method thereof, wherein the preparation method comprises the following steps: step 1, placing a crucible with a pure aluminum ingot in a medium frequency furnace, and heating the pure aluminum ingot on the crucible in stages within a range of 350 to 850° C. by the medium frequency furnace; step 2, introducing an inert gas into a smelting chamber; step 3, continuing to heat the melt in the crucible to 1150 to 1300° C. by the medium frequency furnace, and then successively adding pure manganese flakes and pure zirconium; Step 4, cooling the melt in the crucible to 800-900°C, controlling the pressure in the smelting chamber to 0.3-0.7MPa, and then adding Al-Sc master alloy and Al-Li master alloy; Step 5, continuing to control the melt in the crucible to cool to 700-790°C, and making the pressure in the smelting chamber to 0.05-0.15MPa, and then adding pure magnesium ingot; Step 6, maintaining the crucible at 780-820°C; Step 7, using gas atomization powder making operation for powder making. The present invention aims to make a dense, crack-free, smooth-surfaced formed sample in the process of selective laser melting of aluminum-lithium alloy powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum-lithium alloy powder, and in particular to an aluminum-lithium alloy powder and a preparation method and an application method thereof. Background Art

[0002] At present, selective laser melting (SLM) is a process that uses metal powder to melt layer by layer to prepare metal parts. Compared with traditional production methods, SLM technology can form fully dense near-net-shape components in one piece, solve the forming of many complex structural parts, and greatly reduce the processing procedures and shorten the processing cycle. Therefore, laser additive manufacturing technology has developed rapidly and has been applied in industry. In particular, laser additive manufacturing of aluminum-lithium alloys has become increasingly important in the field of high-performance complex parts manufacturing in various modern industries including automobiles, aerospace, and maritime. Due to the high reflectivity of aluminum-lithium alloy powder to lasers and good thermal conductivity of the material, defects such as cracks and unmelted powder are very likely to occur during the additive manufacturing process.

[0003] At present, the powder materials used for additive manufacturing of aluminum-lithium alloy materials are relatively fixed, generally AlSi10Mg, AlSi7Mg, AlSi12 and other aluminum-silicon alloys. Due to their good welding performance, the additive manufacturing process is relatively mature. However, due to the low mechanical properties of the AlSi series alloys, the mechanical properties of additively manufactured parts are also insufficient, which cannot meet the current high-strength requirements for aluminum-lithium alloy additively manufactured parts. In addition, the use of selective laser melting forming technology to print conventional aluminum-lithium alloy materials is prone to problems such as microcracks and low strength, which limits the promotion and application of aluminum-lithium alloy additive manufacturing technology. Summary of the invention

[0004] The main purpose of the present invention is to provide an aluminum-lithium alloy powder and a preparation method and an application method thereof, aiming to solve the problems of microcracks and low strength of the existing aluminum-lithium alloy powder during the selective laser melting process.

[0005] To achieve the above object, the present invention provides a method for preparing aluminum-lithium alloy powder, the method comprising the following steps:

[0006] Step 1, placing a crucible containing a pure aluminum ingot in a medium frequency furnace, and heating the pure aluminum ingot in the crucible in stages within a range of 350 to 850° C. by the medium frequency furnace to melt the pure aluminum ingot;

[0007] Step 2, introducing an inert gas into the smelting chamber and controlling the pressure in the smelting chamber to be 0.6-0.9 MPa, wherein the intermediate frequency furnace is placed in the smelting chamber;

[0008] Step 3, continue to raise the temperature of the melt in the crucible to 1150-1300° C. by the medium frequency furnace, then successively add pure manganese flakes and pure zirconium, and keep the temperature for 8-15 minutes;

[0009] Step 4, cooling the melt in the crucible to 800-900° C., controlling the pressure in the smelting chamber to 0.3-0.7 MPa, then adding Al-Sc master alloy and Al-Li master alloy, and keeping the temperature for 5-15 minutes after the master alloy is completely melted;

[0010] Step 5, continue to control the temperature of the melt in the crucible to drop to 700-790° C., and make the pressure in the smelting chamber to 0.05-0.15 MPa, and then add pure magnesium ingot;

[0011] Step 6, after the alloy raw materials are completely melted, the crucible is maintained at 780-820°C;

[0012] Step 7, powder making is performed by using aerosol powder making operation.

[0013] Optionally, in step 1, the aluminum ingot on the crucible is preheated in advance by a medium frequency furnace at a preheating temperature of 350-450° C.; then the temperature in the crucible is increased to 700-850° C. to melt the aluminum ingot.

[0014] Optionally, in step (7), the atomizing gas pressure in the gas atomization powder making operation is in the range of 0.5 MPa to 8 MPa.

[0015] Optionally, before step (6), the method further includes: electromagnetically stirring the melt after the alloy raw material is completely melted for 1 to 3 minutes.

[0016] Optionally, step 1 also includes: before preheating, the smelting chamber needs to be evacuated to a vacuum degree below 0.01 Pa, and then an inert gas is filled into the smelting chamber so that the pressure in the smelting chamber is the same as the atmospheric pressure. During the preheating process, the inert gas charging valve and the one-way exhaust valve are opened.

[0017] Optionally, the preheating time is 8-20 minutes.

[0018] Optionally, the mass percentage ratio of Sc and Zr elements in the Al-Sc master alloy and the Al-Li master alloy is 2:1.

[0019] In addition, to achieve the above-mentioned purpose, the present invention also provides an aluminum-lithium alloy powder, which is prepared according to any of the above-mentioned methods for preparing the aluminum-lithium alloy powder.

[0020] Optionally, the mass percentage composition of the aluminum-lithium alloy powder is Li: 0.8%-2.0%, Mg: 4.5-5.5%, Mn: 0.4-1.0%, Sc: 0.2%-1.0%, Zr: 0.1%-0.5%, and the rest is Al and unremovable impurity elements.

[0021] In addition, to achieve the above-mentioned purpose, the present invention also provides an application method of aluminum-lithium alloy powder, which comprises: using the aluminum-lithium alloy powder material described above as a printing material, and using 3D printing to print the printing material into a finished product based on a three-dimensional graphic file to be printed.

[0022] Beneficial effects:

[0023] The present invention improves the microstructure and phase structure of the selective laser melted aluminum-lithium alloy by adding Li element to the high-strength aluminum alloy and adjusting the combination of alloy elements, thereby improving the stiffness of the additively manufactured aluminum alloy, reducing the density, and improving the elastic modulus of the alloy. The principle is that when 1% of Li is added by mass to the aluminum alloy, the alloy density can be reduced by 3%. At the same time, the supersaturated solid solution precipitates the metastable Al3Li phase, which is spherically and evenly dispersed in the matrix to achieve a strengthening effect, thereby improving the elastic modulus of the alloy; and the alloy sample obtained by the present invention is used as a molded sample obtained after 3D printing, and the surface is smooth and crack-free, and the density is high. After heat treatment, the tensile strength, yield strength, elongation, density, elastic modulus, etc. of the aluminum-lithium alloy are compared with the high-strength aluminum alloy. Except for the reduced elongation, the other mechanical properties of the aluminum-lithium alloy are all improved, the stiffness is increased by 16% and the density is reduced by 4%, achieving the comprehensive performance required for production, which is of great significance to broadening the range of selective laser melting forming materials and the application of aluminum-lithium alloys in high-end aerospace components. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Shown is a schematic flow chart of a method for preparing aluminum-lithium alloy powder according to the present invention;

[0025] Figure 2 This is the metallographic image of the formed sample of Example 1;

[0026] Figure 3 This is the metallographic image of the formed sample of Example 2;

[0027] Figure 4 This is the metallographic image of the formed sample of Comparative Example 1;

[0028] Figure 5 This is the metallographic image of the formed sample of Comparative Example 2;

[0029] Figure 6 This is the metallographic image of the formed sample of Comparative Example 3;

[0030] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0031] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.

[0032] See also Figure 1 The present invention provides a method for preparing aluminum-lithium alloy powder, the method comprising the following steps:

[0033] Step 1, placing a crucible with a pure aluminum ingot in a medium frequency furnace, and heating the pure aluminum ingot on the crucible in stages within the range of 350-850°C by the medium frequency furnace; specifically, preheating the aluminum ingot on the crucible by the medium frequency furnace in advance, the preheating temperature is 350-450°C; then raising the temperature in the crucible to 700-850°C to melt the aluminum ingot. In addition, step 1 also includes: before preheating, the smelting chamber needs to be evacuated to below 0.01Pa, and then inert gas is filled into the smelting chamber so that the pressure of the smelting chamber is the same as the atmospheric pressure. During the preheating process, the inert gas charging valve and the one-way exhaust valve are opened, wherein the specific preheating time is 8-20min, and the inert gas introduced is one of nitrogen, helium, and argon. Preferably, argon is used, and preheating allows the pure aluminum ingot to release the included gas, and the high-purity argon gas can replace the included gas in the smelting chamber.

[0034] Step 2, introducing an inert gas into the smelting chamber and controlling the pressure in the smelting chamber to be 0.6-0.9 MPa, wherein the intermediate frequency furnace is placed in the smelting chamber;

[0035] Step 3, continue to raise the temperature of the melt in the crucible to 1150-1300° C. by the medium frequency furnace, then successively add pure manganese flakes and pure zirconium, and keep the temperature for 8-15 minutes;

[0036] Step 4, cooling the melt in the crucible to 800-900° C., controlling the pressure in the smelting chamber to 0.3-0.7 MPa, and then adding Al-Sc master alloy and Al-Li master alloy. After the master alloy is completely melted, keeping the temperature for 5-15 minutes, wherein the mass percentage ratio of Sc and Zr elements in the Al-Sc master alloy and the Al-Li master alloy is 2:1.

[0037] Step 5, continue to control the temperature of the melt in the crucible to drop to 700-790° C., and make the pressure in the smelting chamber to 0.05-0.15 MPa, and then add pure magnesium ingot;

[0038] Step 6, after the alloy raw material is completely melted, the crucible is maintained at 780-820°C; specifically, before step (6), the process also includes: electromagnetically stirring the melt after the alloy raw material is completely melted for 1-3 minutes. The purpose of stirring is to facilitate the uniformity of the alloy components and improve the consistency of the powder after powdering.

[0039] Step 7: Powdering is performed by gas atomization. Specifically, the atomization gas pressure in the gas atomization is in the range of 0.5 MPa to 8 MPa.

[0040] The mass percentage composition of the aluminum-lithium alloy powder finally obtained through the above preparation process is Li: 0.8%-2.0%, Mg: 4.5-5.5%, Mn: 0.4-1.0%, Sc: 0.2%-1.0%, Zr: 0.1%-0.5%, and the rest is Al and unremovable impurity elements.

[0041] Furthermore, the aluminum-lithium alloy powder prepared as above can also be used as a printing material, and the printing material is printed into a finished product based on the three-dimensional graphic file to be printed using 3D printing.

[0042] Example 1

[0043] Preparation of Al-5Mg-0.5Mn-0.7Sc-0.35Zr-1.2Li alloy powder

[0044] Preparation before smelting: clean the smelting furnace in advance, wipe the inner wall of the smelting chamber with a clean cloth moistened with alcohol, wipe the new crucible with a clean cloth moistened with alcohol, and remove the oxide film, ultrasonically clean and dry the smelting raw materials before feeding.

[0045] Melting process:

[0046] Step 1: Add pure aluminum ingots into a crucible, and evacuate the melting chamber to a vacuum degree below 0.01 Pa, then fill the melting chamber with high-purity argon gas so that the pressure in the melting chamber is the same as the atmospheric pressure, and start melting.

[0047] Step 2, first adjust the power of the medium frequency furnace to make the temperature in the crucible 350℃, preheat the pure aluminum ingot, heat the raw materials evenly, release the included gas, and at the same time open the high-purity argon gas charging valve and the one-way exhaust valve to replace the impurity gas overflowed from the metal ingot during heating. After preheating for 10 minutes, increase the smelting power to increase the temperature, and control the temperature at about 850℃ to melt the aluminum ingot.

[0048] Step 3: After the melting starts, a certain amount of high-purity argon is filled into the melting chamber to make the pressure in the melting chamber 0.7MPa to prevent the Al element from volatilizing. After the aluminum ingot is melted, the power is increased to make the melt temperature in the crucible reach 1250°C. Pure manganese flakes and pure zirconium are added from the secondary feeding port and kept warm for 10 minutes.

[0049] Step 4, lower the power of the medium frequency furnace to make the melt temperature in the crucible reach 850°C, adjust the pressure in the smelting chamber to 0.5 MPa, add Al-Sc master alloy and Al-Li master alloy from the secondary feeding port, and keep warm for 10 minutes after the master alloy is melted.

[0050] Step 5, further lower the power of the medium frequency furnace to make the melt temperature in the crucible reach 750°C, adjust the pressure in the smelting chamber to 0.1MPa, and add pure magnesium ingot; adjust the power of the medium frequency furnace to maintain high power for 2 minutes to electromagnetically stir the melt before entering the atomization process.

[0051] Atomization process: Heat the insulated crucible to 800°C during smelting. After the smelting process is completed, start powder making. The atomizing gas pressure is 3.5MPa, and the positive pressure of the smelting chamber is maintained at 9KPa. At the same time, a large flow of cooling water is introduced into the atomizing barrel and the powder collecting tank to ensure the cooling rate of the powder. The atomization time is about 9 minutes. After the atomization is completed, wait for the powder to cool down and complete the powder making. After the prepared powder is screened, the powder yield in the 15-60μm range is about 50%.

[0052] Select the laser melting forming process: the powder is subjected to selective laser melting forming by Renishaw AM400 metal additive manufacturing equipment. The specific forming parameters are: laser spot size 70 μm, laser power 270 W, scanning speed 900 mm / s, scanning line spacing 90 μm, powder layer thickness 30 μm, substrate preheating temperature 150 °C, as shown in FIG. Figure 2 As shown, a dense, crack-free, smooth-surfaced formed sample was obtained. Six tensile test bars were tested, three in the deposited state and three in the heat-treated state. The tensile strength of the deposited test bars was 462MPa, the yield strength was 391MPa, and the elongation was 17.6%. After heat treatment, the tensile strength of the test bars was 577MPa, the yield strength was 542MPa, the elongation was 9.5%, the density was 2.56g / cm3, and the elastic modulus was 78GPa. Among them, the original high-strength aluminum alloy had a tensile strength of 540MPa, a yield strength of 495MPa, an elongation of 11%, a density of 2.67g / cm3, and an elastic modulus of 67GPa. After heat treatment, its tensile strength, yield strength, density, elastic modulus, etc. were compared with high-strength aluminum alloys. Except for the reduced elongation, the other mechanical properties of aluminum-lithium alloys were improved, the stiffness was increased by 16% and the density was reduced by 4%, achieving the comprehensive performance required for production.

[0053] Example 2

[0054] Preparation of Al-5Mg-0.5Mn-0.7Sc-0.35Zr-2Li alloy powder

[0055] Preparation before smelting: clean the smelting furnace in advance, wipe the inner wall of the smelting chamber with a clean cloth moistened with alcohol, wipe the new crucible with a clean cloth moistened with alcohol, and remove the oxide film, ultrasonically clean and dry the smelting raw materials before feeding.

[0056] Melting process:

[0057] Step 1: Add pure aluminum ingots into a crucible, and evacuate the melting chamber to a vacuum degree below 0.01 Pa, then fill the melting chamber with high-purity argon gas so that the pressure in the melting chamber is the same as the atmospheric pressure, and start melting.

[0058] Step 2: During the smelting process, first adjust the power of the medium frequency furnace to make the temperature in the crucible 400°C, preheat the pure aluminum ingot, heat the raw materials evenly, and release the included gas. At the same time, open the high-purity argon gas charging valve and the one-way exhaust valve to replace the impurity gas overflowed from the metal ingot during heating. After preheating for 10 minutes, increase the smelting power to increase the temperature, and control the temperature at about 800°C to melt the aluminum ingot.

[0059] Step 3: After the melting starts, a certain amount of high-purity argon is filled into the melting chamber to make the pressure of the melting chamber 0.9 MPa to prevent the volatilization of Al elements. After the aluminum ingot is melted, the power is increased to make the melt temperature in the crucible reach 1300°C. Pure manganese flakes and pure zirconium are added from the secondary feeding port and kept warm for 15 minutes.

[0060] Step 4, lower the power of the medium frequency furnace to make the melt temperature in the crucible reach 900°C, adjust the pressure of the smelting chamber to 0.7MPa, add Al-Sc master alloy and Al-Li master alloy from the secondary feeding port, and keep warm for 15 minutes after the master alloy is melted.

[0061] Step 5, further lower the power of the medium frequency furnace to make the melt temperature in the crucible reach 790°C, adjust the pressure in the smelting chamber to 0.1MPa, and add pure magnesium ingot; adjust the power of the medium frequency furnace to maintain high power for 2 minutes to electromagnetically stir the melt before entering the atomization process.

[0062] Atomization process: Heat the insulated crucible to 820°C during smelting. After the smelting process is completed, start powder making. The atomizing gas pressure is 8MPa, and the positive pressure of the smelting chamber is maintained at 9KPa. At the same time, a large flow of cooling water is introduced into the atomizing barrel and the powder collecting tank to ensure the cooling rate of the powder. The atomization time is about 9 minutes. After the atomization is completed, wait for the powder to cool down and complete the powder making. After the prepared powder is screened, the powder yield in the range of 15-60μm is about 50%.

[0063] Select the laser melting forming process: the powder is subjected to selective laser melting forming by Renishaw AM400 metal additive manufacturing equipment. The specific forming parameters are: laser spot size 70 μm, laser power 250 W, scanning speed 900 mm / s, scanning line spacing 90 μm, powder layer thickness 30 μm, substrate preheating temperature 150 °C, as shown in FIG. Figure 3 As shown, a dense, crack-free, smooth-surfaced formed sample was obtained. After forming, 6 tensile test bars were tested, 3 in the deposited state and 3 in the heat-treated state. The tensile strength of the deposited test bars was 478MPa, the yield strength was 406MPa, and the elongation was 16.5%; after heat treatment, the tensile strength of the test bars was 592MPa, the yield strength was 554MPa, the elongation was 5.2%, the density was 2.50g / cm3, and the elastic modulus was 85GPa. Among them, the original high-strength aluminum alloy had a tensile strength of 540MPa, a yield strength of 495MPa, an elongation of 11%, a density of 2.67g / cm3, and an elastic modulus of 67GPa. After heat treatment, its tensile strength, yield strength, density, elastic modulus, etc. were compared with high-strength aluminum alloys. Except for the reduced elongation, the other mechanical properties of aluminum-lithium alloys were improved, the stiffness was increased by 16% and the density was reduced by 4%, achieving the comprehensive performance required for production.

[0064] Comparative Example 1

[0065] Preparation of Al-5Mg-0.5Mn-0.7Sc-0.35Zr-3Li alloy powder

[0066] Preparation before smelting: clean the smelting furnace in advance, wipe the inner wall of the smelting chamber with a clean cloth moistened with alcohol, wipe the new crucible with a clean cloth moistened with alcohol, and remove the oxide film, ultrasonically clean and dry the smelting raw materials before feeding.

[0067] Melting process:

[0068] Step 1: Add pure aluminum ingots into a crucible. After the vacuum degree of the melting chamber reaches below 0.01 Pa, high-purity argon gas is filled into the melting chamber to make the pressure in the melting chamber the same as the atmospheric pressure, and then start melting.

[0069] Step 2, first adjust the power of the medium frequency furnace to make the temperature in the crucible 500℃, preheat the pure aluminum ingot, heat the raw materials evenly, release the included gas, and at the same time open the high-purity argon gas charging valve and the one-way exhaust valve to replace the impurity gas overflowed from the metal ingot during heating. After preheating for 10 minutes, increase the smelting power to increase the temperature, and control the temperature at about 900℃ to melt the aluminum ingot.

[0070] Step 3: After the melting starts, a certain amount of high-purity argon is filled into the melting chamber to make the pressure of the melting chamber 1.7MPa to prevent the Al element from volatilizing. After the aluminum ingot is melted, the power is increased to make the melt temperature in the crucible reach 1350°C. Pure manganese flakes and pure zirconium are added from the secondary feeding port and kept warm for 10 minutes.

[0071] Step 4, lower the melting power to make the melt temperature in the crucible reach 950°C, adjust the melting chamber pressure to 1.5MPa, add Al-Sc master alloy and Al-Li master alloy from the secondary feeding port, and keep warm for 10 minutes after the master alloy is melted.

[0072] Step 5, further lower the power of the medium frequency furnace to make the melt temperature in the crucible reach 950°C, adjust the pressure in the smelting chamber to 0.1MPa, and add pure magnesium ingot; adjust the power of the medium frequency furnace to maintain high power for 2 minutes to electromagnetically stir the melt before entering the atomization process.

[0073] Atomization process: Heat the insulated crucible to 900°C during smelting. After the smelting process is completed, start powder making. The atomizing gas pressure is 3.5MPa, and the positive pressure of the smelting chamber is maintained at 9KPa. At the same time, a large flow of cooling water is introduced into the atomizing barrel and the powder collecting tank to ensure the cooling rate of the powder. The atomization time is about 9 minutes. After the atomization is completed, wait for the powder to cool down and complete the powder making. After the prepared powder is screened, the powder yield in the 15-60μm range is about 50%.

[0074] Select the laser melting forming process: the powder is subjected to selective laser melting forming by Renishaw AM400 metal additive manufacturing equipment. The specific forming parameters are: laser spot size 70 μm, laser power 230 W, scanning speed 900 mm / s, scanning line spacing 90 μm, powder layer thickness 30 μm, substrate preheating temperature 150 °C, and its microstructure is observed by metallographic microscope, such as Figure 4 As shown, obvious microcracks were found and a dense sample could not be formed.

[0075] Comparative Examples 2-3

[0076] The traditional aluminum-lithium alloy Weldalite210 (Al-4.5Cu-1.3Li-0.4Mg-0.4Ag) and aluminum-lithium alloy 2195 (Al-4Cu-1Li-0.8Mg-0.4Ag-0.14Zr) were prepared by powder and subjected to additive manufacturing forming experiments. The microstructure of the formed samples was observed. The results show that after the Weldalite210 and 2195 aluminum-lithium alloy powders were formed, their microstructures were observed by metallographic microscope, such as Figure 5-6 As shown, obvious cracks were found and a dense sample could not be formed.

[0077] Based on the above content, it can be seen that the aluminum-lithium alloy powder prepared by the preparation method of the present application improves the microstructure and phase structure of the selective laser melted aluminum-lithium alloy by adding Li element and adjusting the combination of alloy elements, thereby improving the stiffness of the additively manufactured aluminum alloy, reducing the density, and improving the elastic modulus of the alloy, thereby making the surface of the molded sample obtained by 3D printing using the alloy sample obtained by the present invention smooth, crack-free, and high in density.

[0078] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or system including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or system. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or system including the element.

[0079] The serial numbers of the above embodiments of the present invention are only for description and do not represent the advantages or disadvantages of the embodiments.

[0080] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing aluminum-lithium alloy powder, characterized in that: The method comprises the following steps: Step 1, placing a crucible containing a pure aluminum ingot in a medium frequency furnace, and heating the pure aluminum ingot in the crucible in stages within a range of 350 to 850° C. by the medium frequency furnace to melt the pure aluminum ingot; Step 2, introducing an inert gas into the smelting chamber and controlling the pressure in the smelting chamber to be 0.6-0.9 MPa, wherein the intermediate frequency furnace is placed in the smelting chamber; Step 3, continue to raise the temperature of the melt in the crucible to 1150-1300° C. by the medium frequency furnace, then successively add pure manganese flakes and pure zirconium, and keep the temperature for 8-15 minutes; Step 4, cooling the melt in the crucible to 800-900° C., controlling the pressure in the smelting chamber to 0.3-0.7 MPa, then adding Al-Sc master alloy and Al-Li master alloy, and keeping the temperature for 5-15 minutes after the master alloy is completely melted; Step 5, continue to control the temperature of the melt in the crucible to drop to 700-790° C., and make the pressure in the smelting chamber to 0.05-0.15 MPa, then add pure magnesium ingots, and then electromagnetically stir the melt after the alloy raw materials are completely melted for 1-3 minutes; Step 6, after the alloy raw materials are completely melted, the crucible is maintained at 780-820°C; Step 7, using gas atomization powder making operation to make powder to obtain aluminum-lithium alloy powder, the atomization gas pressure in the gas atomization powder making operation is in the range of 0.5MPa to 8MPa; Among them, the mass percentage ratio of Sc and Zr elements in the Al-Sc master alloy and the Al-Li master alloy is 2:1, and the mass percentage composition of the aluminum-lithium alloy powder is Li: 0.8%-2.0%, Mg: 4.5-5.5%, Mn: 0.4-1.0%, Sc: 0.2%-1.0%, Zr: 0.1%-0.5%, and the rest are Al and non-removable impurity elements, and each addition of 1% of Li by mass fraction can reduce the alloy density by 3%, and the alloy powder has a metastable Al3Li phase, which is spherical and uniformly dispersed in the matrix and is used to improve the elastic modulus of the alloy.

2. The method for preparing aluminum-lithium alloy powder according to claim 1, characterized in that: In the step 1, the aluminum ingot on the crucible is preheated in advance by a medium frequency furnace at a temperature of 350-450° C.; then the temperature in the crucible is increased to 700-850° C. to melt the aluminum ingot.

3. The method for preparing aluminum-lithium alloy powder according to claim 2, characterized in that: The step 1 also includes: before preheating, the smelting chamber needs to be evacuated to a vacuum degree below 0.01 Pa, and then an inert gas is filled into the smelting chamber so that the pressure of the smelting chamber is the same as the atmospheric pressure. During the preheating process, the inert gas charging valve and the one-way exhaust valve are opened.

4. The method for preparing aluminum-lithium alloy powder according to claim 2 or 3, characterized in that: The preheating time is 8-20 minutes.

5. An aluminum-lithium alloy powder, characterized in that: The aluminum-lithium alloy powder is obtained according to the method for preparing the aluminum-lithium alloy powder according to any one of claims 1 to 4.

6. A method for applying aluminum-lithium alloy powder, characterized in that: The application method comprises: using the aluminum-lithium alloy powder material according to claim 5 as a printing material, and using 3D printing to print the printing material into a finished product based on a three-dimensional graphic file to be printed.

Citation Information

Patent Citations

  • Al-Cu-Li-Sc-Zr aluminum alloy powder for additive manufacturing and preparation method thereof

    CN109402472A

  • Aging treatment technology of Al-Mg-Li-Yb alloy

    CN110423964A